The first full study of heavy metal(loid)s in western-European hedgehogs (Erinaceus europaeus) from Portugal - Baptista, Catarina Jota (2024)
The western-European hedgehog (Erinaceus europaeus) is an insectivore with a wide distribution in Portugal and a potential tool for biomonitoring relevant One Health hazards, including heavy metal(loid)s’ pollution. The aim of this study was to positively contribute to the current knowledge about the metal(loid) pollution in Portugal. Forty-six hedgehogs (from rescue centres; with known provenance) were necropsied. Sex, age category and weight were determined. Spines, liver and kidney were collected, and metalloid concentrations were determined by inductively coupled plasma mass spectrophotometry (ICPMS). In general, results did not present alarming metal(loid) concentrations, with the exception of cadmium (Cd) (in the kidneys) and copper (Cu). Hedgehogs from Viana do Castelo and Viseu showed elevated concentrations of arsenic (As) and Castelo Branco presented concerning values of cadmium (Cd). Adult and heavier hedgehogs tended to present higher levels of metal(loid)s. Sex does not seem to significantly affect the metal(loid)s’ concentrations. Further analysis would be needed to prioritize areas with detail and allow the application of the necessary mitigation strategies.